Psychometric Evaluation of the Affect Regulation Checklist: Clinical and Community Samples, Parent‐Reports and Youth Self‐Reports. (14th June 2022) - Goulter, Natalie; Balanji, Sherene; Davis, Brooke A.; James, Tim; McIntyre, Cassia L.; Smith, Erica; Thornton, Emily M.; Craig, Stephanie G.; Moretti, Marlene M.
Abstract : The Affect Regulation Checklist (ARC) was designed to capture affect dysregulation, suppression, and reflection. Importantly, affect dysregulation has been established as a transdiagnostic mechanism underpinning many forms of psychopathology. We tested the ARC psychometric properties across clinical and community samples and through both parent‐report and youth self‐report information. Clinical sample: Participants included parents ( n  = 814; M age   =  43.86) and their child ( n  = 608; M age  = 13.98). Community sample: Participants included independent samples of parents ( n  = 578; M age   =  45.12) and youth ( n  = 809; M age  = 15.67). Exploratory structural equation modeling supported a three‐factor structure across samples and informants. Dysregulation was positively associated with all forms of psychopathology. In general, suppression was positively associated with many forms of psychopathology, and reflection was negatively associated with externalizing problems and positively associated with internalizing problems.